2014
DOI: 10.3109/08990220.2014.905469
|View full text |Cite
|
Sign up to set email alerts
|

Whisker-related circuitry in the trigeminal nucleus principalis: Ultrastructure

Abstract: Trigeminal (V) nucleus principalis (PrV) is the requisite brainstem nucleus in the whisker-to-barrel cortex model system that is widely used to reveal mechanisms of map formation and information processing. Yet, little is known of the actual PrV circuitry. In the ventral "barrelette" portion of the adult mouse PrV, relationships between V primary afferent terminals, thalamic-projecting PrV neurons, and gamma-aminobutyric acid (GABA)-ergic terminals were analyzed in the electron microscope. Primary afferents, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Moreover, further differences exist between V ganglion and PrV cells in the extent to which they display spontaneous activity, directional sensitivity, and tonic vs. phasic adaptation to a sustained stimulus. In a recent ultrastructural analysis of identified circuits within PrV barrelettes (Xiang et al 2014), we suggested five possible ways that the receptive fields of PrV cells could be so transformed: (1) Terminal clusters from primary afferents innervating neighboring whiskers overlap in the PrV's somatotopic coronal plane; thus, single whisker afferents span multiple barrelettes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, further differences exist between V ganglion and PrV cells in the extent to which they display spontaneous activity, directional sensitivity, and tonic vs. phasic adaptation to a sustained stimulus. In a recent ultrastructural analysis of identified circuits within PrV barrelettes (Xiang et al 2014), we suggested five possible ways that the receptive fields of PrV cells could be so transformed: (1) Terminal clusters from primary afferents innervating neighboring whiskers overlap in the PrV's somatotopic coronal plane; thus, single whisker afferents span multiple barrelettes.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, sensory gating might act via PAD as well, although, the existence of a PAD-based mechanism is uncertain. The synaptic elements potentially suitable for PAD have been demonstrated 43 , but neither have their functional properties been shown to be suited for PAD nor have their origins been delineated. Pr5 itself contains only a small number of inhibitory neurons 32 , and our finding of a lack of gating and motor-related responses in Sp5i putative inhibitory neurons does not support a mechanism based on an inhibitory cascade involving Sp5i 28 , although these projections could still play a potential role, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Many unexplored inhibitory brainstem targets of corticofugal projections may in principle be involved, amongst them Sp5c, which has been reported to project also directly to Pr5 32 . Other than PAD, mechanisms such as postsynaptic modulation might also play a role particularly given that primary afferents terminate on distal dendrites and spines of Pr5 neurons 43 . Finally, corticofugal projections to Pr5 27 may act directly (e.g.…”
Section: Discussionmentioning
confidence: 99%